Hans Luther, ett hundraårsminne - Hæggström, Carl-Adam; Munsterhjelm, Riggert (Memoranda Societatis pro Fauna et Flora Fennica, 2016)
Hans Luther, a centenary Hans Edmund Luther (July 2, 1915 – June 9, 1982) was Professor in Botany (chair with Swedish as statutory language) at Helsinki University 1961–1978. Hans Luther’s main topic was the ecology and distribution of brackish water macrophytes of the Baltic Sea, mainly in the Pojoviken – Tvärminne area on the southwestern coast of mainland Finland. He studied also algae, e.g. the Xanthophyceae, fungi and terrestrial vascular plants, especially some of polemochorous origin and other ruderals. This paper by two of his pupils describe his career as a scientist and university teacher. Some anecdotes about him are also dealt with. A list of Hans Luther´s publications is included.